SUPPORTING STUDENTS' PSYCHOLOGICAL WELL-BEING IN THE PROCESS OF DISTANCE LEARNING DURING WAR - Олексенко, Світлана; Сабол, Діана; Хоменко, Олена (SWorldJournal, 2025)
The article considers the problem of supporting the psychological well-being of students in the process of distance learning. The methods and techniques that teachers use to ensure emotional stability, motivation and positive mood of children during onlin